New Frontiers in Artificial Intelligence JSAI-isAI 2012 Workshops, LENLS, JURISIN, MiMI, Miyazaki, Japan, November 30 and December 1, 2012, Revised Selected Papers - Motomura, Yoichi; Butler, Alastair; Bekki, Daisuke (Lecture Notes in Artificial Intelligence,, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the JSAI-isAI 2012 Workshops LENLS, JURISIN, ALSIP, MiMI, which tool place on November/December 2012, respectively, in Miyazaki, Japan. The 17 contributions in this volume were carefully reviewed and selected from 42 submissions.They are an excellent selection of papers that are representative of topics of AI research both in Japan an in other parts of the world. LENLS (Logic and Engineering of Natural Language Semantics) is an annual international workshop on formal semantics and pragmatics; its topics are the formal and theoretical aspects of natural language. JURISIN (Juris-Informatics) deals with juris-informatics. This workshop brings together people from various backgrounds such as law, social science, information and intelligent technology, logic and philosophy, including the conventional "AI and law" area. MiMI (Multimodality in Multispace Interaction) focuses on how multispace is managed in socially, temporally, and sequentially complex environments.